Plant nuclear envelope as a hub connecting genome organization with regulation of gene expression - Yu Tang (Nucleus, 2023)
ABSTRACTEukaryotic cells organize their genome within the nucleus with a double-layered membrane structure termed the nuclear envelope (NE) as the physical barrier. The NE not only shields the nuclear genome but also spatially separates transcription from translation. Proteins of the NE including nucleoskeleton proteins, inner nuclear membrane proteins, and nuclear pore complexes have been implicated in interacting with underlying genome and chromatin regulators to establish a higher-order chromatin architecture. Here, I summarize recent advances in the knowledge of NE proteins that are involved in chromatin organization, gene regulation, and coordination of transcription and mRNA export. These studies support an emerging view of plant NE as a central hub that contributes to chromatin organization and gene expression in response to various cellular and environmental cues.